Selective Blockade of TNFR1 Improves Clinical Disease and Bronchoconstriction in Experimental RSV Infection - Dorothea R. Morris; Maria Ansar; Teodora Ivanciuc; Yue Qu; Antonella Casola; Roberto P. Garofalo (Viruses, 2020)
Respiratory syncytial virus (RSV) is the leading cause of bronchiolitis in infants and young children. Although some clinical studies have speculated that tumor necrosis factor (TNF)-α is a major contributor of RSV-mediated airway disease, experimental evidence remains unclear or conflicting. TNF-α initiates inflammation and cell death through two distinct receptors: TNF-receptor (TNFR)1 and TNFR2. Here we delineate the function of TNF-α by short-lasting blockade of either receptor in an experimental BALB/c mouse model of RSV infection. We demonstrate that antibody-mediated blockade of TNFR1, but not TNFR2, results in significantly improved clinical disease and bronchoconstriction as well as significant reductions of several inflammatory cytokines and chemokines, including IL-1α, IL-1β, IL-6, Ccl3, Ccl4, and Ccl5. Additionally, TNFR1 blockade was found to significantly reduce neutrophil number and activation status, consistent with the concomitant reduction of pro-neutrophilic chemokines Cxcl1 and Cxcl2. Similar protective activity was also observed when a single-dose of TNFR1 blockade was administered to mice following RSV inoculation, although this treatment resulted in improved alveolar macrophage survival rather than reduced neutrophil activation. Importantly, short-lasting blockade of TNFR1 did not affect RSV peak replication in the lung. This study suggests a potential therapeutic approach for RSV bronchiolitis based on selective blockade of TNFR1.